(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
According to the United Nations World Tourism Organization, cultural tourism is “movements of persons for essentially cultural motivations such as study tours, performing arts and cultural tours, travel to festivals and other cultural events, visits to sites and monuments, travel to study nature, folklore or art.